2018
DOI: 10.13005/bpj/1502
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Spermidine and Spermine in Association with Atherosclerosis in Sera of Iraqi Patients

Abstract: This study aims to determine the relationship between spermidine (SPD) and spermine (SPM) with the incidence of atherosclerosis in population of Iraqi patients in comparison with controls. A total of 128 atherosclerosis patients (64 male and 64 female) were included in the present study (aged 45-70 years). They were categorized into two groups: a group that underwent percutaneous coronary intervention catheterization (PCI) and a group that underwent diagnostic catheterization (DIG). 64 age matched, apparently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In particular, a recent study showed serum levels of spermidine and spermine at >500 µg ml −1 —close to their respective MICs in AB5075-UW amvA or adeB mutants (Fig. 3b ) 57 . Alternatively, efflux of endogenous polyamines by AmvA (and perhaps AdeABC) may provide adaptive advantages unrelated to detoxification.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In particular, a recent study showed serum levels of spermidine and spermine at >500 µg ml −1 —close to their respective MICs in AB5075-UW amvA or adeB mutants (Fig. 3b ) 57 . Alternatively, efflux of endogenous polyamines by AmvA (and perhaps AdeABC) may provide adaptive advantages unrelated to detoxification.…”
Section: Discussionsupporting
confidence: 64%
“…Such systems may protect from exogenous polyamines encountered in host environments. Polyamine levels can reach the mM range in plants, the gut, and in serum of patients suffering from some diseases 54 – 57 . In particular, a recent study showed serum levels of spermidine and spermine at >500 µg ml −1 —close to their respective MICs in AB5075-UW amvA or adeB mutants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, marked sex differences for N-acetylated polyamines in human urine were identified by Paik et al [13]. Ibrahim et al [47] reported that the SPD and SPM serum levels differed significantly according to sex in atherosclerosis patients. In contrast, Magnes et al [27] assessed sex differences in the human serum samples of obese patients and found no significant differences in polyamine concentration between males and females.…”
Section: Methods Applicationmentioning
confidence: 99%
“…Such systems may protect from toxic levels of exogenous polyamines encountered in host environments. Polyamine levels can reach the mM range in plants, the gut, and in serum of patients suffering from some diseases (44)(45)(46)(47). In particular, a recent study showed serum levels of spermidine and spermine at >500 µg/ml -close to their respective MICs in AB5075-UW amvA or adeB mutants (Fig 3B) (47).…”
Section: Baumanniimentioning
confidence: 97%
“…Polyamine levels can reach the mM range in plants, the gut, and in serum of patients suffering from some diseases (44)(45)(46)(47). In particular, a recent study showed serum levels of spermidine and spermine at >500 µg/ml -close to their respective MICs in AB5075-UW amvA or adeB mutants (Fig 3B) (47). Alternatively, efflux of endogenous polyamines by AmvA (and perhaps AdeABC) may provide adaptive advantages unrelated to detoxification.…”
Section: Baumanniimentioning
confidence: 99%